Ayurvedic management of (AbhigatajSnayuGata Vata) Anterior Cruciate Ligament Injury: - A Case Study - Farhan, Mohammed; Maksane, Sushant; Bansal, Priyal; Borkar, Preeti (Journal of Neonatal Surgery, 2025)
Knee joint is one of the body's biggest and most intricate joints. Because of their significance in ensuring knee stability, the anterior and posterior cruciate ligaments of the knee are frequently referred as the "crucial" ligaments. Every Samhita and Sangraha Grantha mention Snayugata Vata under Vatavyadhi. When agitated or irritated by anything internal or external, vata component residing in Snayu causing immediate Snayugata Vata's manifestation. According to Sushruta, Snayugata Vata is, lodge in Snayu then sthambha (stiffness) angered Vata. The creation of Kampa (tremors), Shoola (pain), and Akshep (involuntary movements) the affliction of Snayu by Prakupita Vata is the chief phenomena in Samprapti of Snayugata Vata.The main causes of knee ligament injuries are indirect, bending or twisting stresses on the knee or often rotating movements of the knee joint. Complete ACL rupturecan lead to other knee diseases. Here is a case study of a 26-year-old women who injured his left knee while driving a vehicle and had severe pain and a pop sound at period of occurrence. When she arrived to the hospital, the knee was enlarged and having a lot of pain in, movement. She was found to have a partial ACL injury on the MRI. The patient was given a Tailadhara, Abhyanga (oil massage), lepa (external application) and some internal medicine that lasted one month. The patient was stable enough to resume his normal activities and also got relieved from the pain and swelling